PENGARUH PEMBERIAN PUPUK PHOSPAT DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI BENGKUANG (Pachyrhizus erosus (L.) Urban.) - Dwi Wahyu Prabowo; T. Chairun Nisa B; Jonathan Ginting (Jurnal Agroekoteknologi, 2013)
This study aimed to determine the most suitable planting distace and dose of phospate fertilizer forthe growth and yield of yam. The reasearch was conducted at Jln. Setia Budi, Simpang Selayang,Medan Tuntungan at ± 25 meters above sea level from April until August 2012. The research usedthe factorial completely randomized block design with two factors, namely phospate fertilizer (0g,5,3g, 10,67g, and 16 g/plot) and planting distance (20x15 cm, 20x20 cm, and 20x25 cm).Parameters observed were plant length, number of branches, tuber weight per sample, tuber weightper plot, tuber diameter , root volume and   and harvest index. The results showed that phospatefertilizer treatment did not show any significant effects for all parameters. Longer planting distancesignificantlly increased plant lengths only at 3 and 4 WAP, but not at other ages, and for all otherparameters as well. Similirlly, there was no significant interaction effect of the two treatments for all parameters.Key words : phospate fertilizer, planting distance, yam